Determinants of jaundice severity in neonates admitted at a Teaching Hospital in Ghana - Naomi Safo-Mensah; Olivia Amfo-Swanzy; Joyce Ashong; Emmanuel Okai; Manuella Faith Amoako; Percy Lomotey; Oheneba Charles Kofi Hagan; George Adjei (PLoS ONE, 2025)
Background Severe neonatal jaundice (NJ) is associated with significant morbidity and mortality globally with low and, middle income countries having a greater burden. Increased red blood cell destruction and reduced bilirubin elimination increase the risk of severe NJ development. Severe NJ predisposes the neonates to bilirubin-induced encephalopathy leading to kernicterus-spectrum disorders in the long-term. Objective The study was undertaken to determine the risk factors associated with development of significant jaundice in neonates at a teaching hospital in Ghana. Materials and methods A retrospective review of patient electronic medical records at the paediatric ward and Neonatal Intensive Care Unit (NICU) at the Cape Coast Teaching Hospital (CCTH) was conducted. Demographics, initial serum bilirubin concentration (total, direct and indirect), full blood count, G6PD status and outcome data were collected. Binary logistic regression models were used to determine the risk factors of NJ severity which was the main outcome. Stata 18.0 software was used for the analysis. Results Data on two hundred and ninety-three (293) neonates were extracted of which 247 were used for further analyses after data cleaning. Of these, 30% had significant NJ defined as initial TSB concentration ≥ 213micromol/L. Significant NJ was significantly associated with admission after 24 hours of birth (aOR = 2.45; 95% CI:1.26,4.77; p = 0.009) and full/partial defect G6PD (aOR = 2.21; 95% CI:1.03,4.71; p = 0.041). Conclusions Significant NJ is common and significantly associated with admission after 24 hours of life and G6PD full/partial defect at Cape Coast Teaching Hospital.